Implementasi Sistem Manajemen Informasi Sekolah (SMIS): Analisis Permasalahan dan Strategi Pengelolaan di SMA Karya Pengalihan Kecamatan Keritang Indragiri Hilir - Safitri, Rani Aulia; Rahmanasari, Dian; Tusakdiah, Halima (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2026)
This study examines the suboptimal implementation of the School Management Information System (SMIS) at SMA Karya Pengalihan, Keritang District, Indragiri Hilir. The limitations are reflected in inadequate infrastructure, low human resource competence, and the lack of system integration in school management. The research aims to analyze SMIS implementation, identify existing challenges, and examine management strategies. A qualitative approach with a case study design was employed. The study involved five informants, principal, vice principal, SMIS operator, teacher, and administrative staff—selected through purposive sampling. Data collection techniques included observation, in-depth interviews, and documentation, while data analysis followed the Miles and Huberman model. The findings indicate that SMIS implementation remains limited to basic administrative functions and faces challenges related to infrastructure, user competence, limited training, and resistance to change. Existing management strategies are still technical and have not addressed policy development or human resource capacity strengthening.